Expression of the forkhead transcription factor FOXP1 is associated with that of estrogen receptor-beta in primary invasive breast carcinomas. - Bates, G; Fox, S; Han, C; Launchbury, R; Leek, R; Harris, A; Banham, A (2008)
We previously identified a correlation between estrogen receptor alpha (ERalpha) and the candidate tumour suppressor gene Forkhead Box P1 (FOXP1), whose nuclear protein expression in breast tumours was associated with improved patient survival. However, the expression pattern of FOXP1 in normal breast tissue is more reminiscent of the second receptor, ERbeta, which has an emerging role as a tumour suppressor in breast cancer and critically may underlie the ability of some ERalpha-negative tumours to respond to tamoxifen. In a series of 283 breast cancers, in which ERalpha-positive tumours were treated with tamoxifen, the nuclear expression of ERbeta correlated significantly with ERalpha (p = 0.004), low-tumour grade (p = 0.008) and nuclear FOXP1 (p = 0.01). High-grade tumours exhibited significantly more cytoplasmic ERbeta than the low-grade tumours (p = 0.006). Regression analysis demonstrated that FOXP1 expression was most closely related to nuclear ERbeta (p = 0.021). Neither, nuclear or cytoplasmic ERbeta expression demonstrated prognostic significance. FOXP1 is not estrogen regulated and silencing FOXP1 expression, using siRNA, did not affect ERalpha, ERbeta or progesterone receptor expression, suggesting ER and FOXP1 co-expression may reflect a common regulatory mechanism.